Risk Associated with NAD (P) H: Quinone Oxidoreductase I (NQOI) C609T Polymorphism for Cigarette Smoke Induced Cardiovascular Disease (CVD): A Study on Male Current Smokers from Eastern India: Life Sciences-Genetics for Medical science - Santanu Banerjee (International Journal of Life Science and Pharma Research, 2022)
NAD(P)H: quinone oxidoreductase 1 (NQO1) is a well-known enzyme for its protective role against cigarette smoke (CS) derived harmful quinones such as p-benzoquinone which is a major causative agent of CS-related cardiovascular disease (CVD). NQO1 C609T single nucleotide polymorphism has severe consequence on NQO1 function and its availability. We propose that the presence of the variant allele of this polymorphism exposes smokers towards a greater risk of developing CVD. For the verification of this hypothesis we perform a genotype analysis for this SNP in two groups of male current smokers (smokers with CVD, n=100 and smokers without CVD, n=200) by a PCR-RFLP method. Genotype distributions of both groups were in Hardy Weinberg equilibrium. The wild type (p) and the variant allele (q) frequencies were different for these two groups (in smokers without CVD: p=67.3%, q=32.7%; in smokers with CVD: p=59%, q=41%). The genotype frequencies were significantly different between the two smoker groups (in smoker without CVD: CC=43.5%, CT=47.5% and TT=9%; in smokers with CVD: CC=32%, CT=54% and TT=14%). Cochran-Armitage-linear Trend Test indicated that the ‘proportions of smokers with CVD’ have a linear trend with the number of variant alleles of NQO1 C609T SNP (CA Test χ2=4.329, p<0.05). The variation of genotype distribution between the two smoker groups was analysed by different genetic test model. Significant variation was observed in additive model (p<0.05). The odds ratios (OR) for the heterozygous (CT) and the homozygous (TT) were greater than one (for CT: OR=1.55, 95%CI: 0.91-2.61; for TT: OR=2.11, 95%CI: 0.94-4.74).Thus, the study strongly indicated that the variant allele of the NQO1 C609T SNP is associated with greater risk for developing CS- related CVD in cigarette smokers.